ISOLASI, ENUMERASI DAN DETEKSI MOLEKULER GEN ToxR PADA BAKTERI Vibrio parahaemolyticus DARI TAMBAK UDANG VANNAMAE DI REMBANG - Thu'ti Alawiyyah; Anto Budiharjo; Agung Suprihadi (Jurnal Akademika Biologi, 2017)
The presence of opportunistic pathogen bacteria in shrimp pond water is caused by 3 factor. There is environmental factor, shrimp condition and the existence of bacteria. Vibrosis disesase in shrimp is harmfull to farmers because it makes reducing result and caused disease in humans. Bacteria often found among types of Vibrio. The toxR gene is known as the transmembrane regulator gene that control the expression of toxin gene. This study aims to determine the existence of toxR gene in Vibrio parahaemolyticus in pond water samples by PCR method. Bacterial isolation was performed using selective media CDVP Nissui. Enumeration of bacteria by TPC method to determine the number of suspected V. parahaemolyticus on CDVP. Extraction of bacterial DNA using QIAamp® DNA Mini Kit. A good qualitative result of the DNA extraction then amplified by toxR primer. Sequencing process sent to PT. Genetica Science. V. parahaemolyticus inoculated on CDVP media showed blue-green color because it can not ferment sucrose. Dry media CDVP Nissui can be used as a medium in the enumeration of Vibrio parahaemolyticus (1,6 x 102 CFU/ml in water sample) because it can be distinguished by the type of bacteria colony color that appears. The PCR protocol used was annealing at 62ºC with a cycle 30 times. Electrophoresis results showed that bacterial samples from pond water positively containing toxR gene with length 368 bp. From sequence base data of nucleotides, the sample has 99% equation with V. parahaemolyticus in the NCBI bank gene. Samples of V. parahaemolyticus bacteria in shrimp pond water in Rembang are known contain the toxR gene.Keyword : V. parahaemolyticus, toxR gene, enumeration, TCBS, CDVP